Emerging Trends of using Digital Tools including Artificial Intelligence in Health sector in Nepal: What Next? - Adhikari, Lal Mani (NPRC Journal of Multidisciplinary Research, 2025)
The integration of AI and digital technology in Nepal's primary health care system has significantly enhanced diagnostic capabilities, enabling early diagnosis and treatment. The study highlights the use of AI, databases, telemedicine, and mobile apps for disease diagnosis and prevention. AI platforms, particularly those processing radiological images, are the most widely adopted tools. While these technologies have the potential to revolutionize healthcare by improving efficiency, accuracy, and patient outcomes, addressing the existing gaps in policies, regulations and ethical considerations is essential for maximizing their benefits. Further studies are recommended to generate the systematic evidences of adopting digital health solutions for enhancing Nepal’s healthcare system.